2023
DOI: 10.1101/2023.01.03.522608
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Calponin 2 harnesses metabolic reprogramming to determine kidney fibrosis

Abstract: In the fibrotic kidneys, the extent of a formed deleterious microenvironment is determined by cellular mechanical forces. This process requires metabolism for energy; however, how cellular mechanics and metabolism are connected remains unclear. Our proteomics revealed that actin filament binding and cell metabolism are the two most dysregulated events in the fibrotic kidneys. As a prominent actin stabilizer, Calponin 2 (CNN2) is predominantly expressed in fibroblasts and pericytes. CNN2 knockdown preserves kid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Understanding CNN2-mediated discrete fine-tuning of protein posttranslational modification is critical to optimize organ performance after AKI. JCI Insight 2023;8 (21):e170521 https://doi.org/10.1172/jci.insight.170521 (FAO) (5). Surprisingly, after AKI, our proteomics showed that CNN2 knockdown had a minor effect on FAO but markedly induced 3-hydroxy-3-methylglutaryl-CoA synthase 2 (Hmgcs2) in the kidney, a rate-limiting enzyme in ketogenesis.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Understanding CNN2-mediated discrete fine-tuning of protein posttranslational modification is critical to optimize organ performance after AKI. JCI Insight 2023;8 (21):e170521 https://doi.org/10.1172/jci.insight.170521 (FAO) (5). Surprisingly, after AKI, our proteomics showed that CNN2 knockdown had a minor effect on FAO but markedly induced 3-hydroxy-3-methylglutaryl-CoA synthase 2 (Hmgcs2) in the kidney, a rate-limiting enzyme in ketogenesis.…”
Section: Introductionmentioning
confidence: 87%
“…Over the past several years, sporadic reports revealed the translational value of CNN2 from the perspective of cell mechanics, such as inhibiting tumor metastasis (3). Emerging evidence indicates that CNN2 is linked to various fibrotic processes, such as postoperative peritoneal adhesions and kidney fibrosis (4,5). In chronic kidney disease (CKD), CNN2 regulates energy metabolism by interacting with estrogen receptor 2 (ESR2) to control fibrosis progression (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical staining showed protein expression patterns consistent with western blot assays of the septic livers (Figure 3F). Given the liver is the central organ that controls lipid homeostasis, we further examined the expression of a prominent protein linked to lipid deposition, perilipin 2, 40,41 in the septic livers. Perilipin 2 was dramatically induced at d2 after CLP and reduced to basal level at d7 (Figure 3G,H), consistent with our finding in the global proteomic analysis.…”
Section: The Significant Proteins Involved In Liver Injury and Repair...mentioning
confidence: 99%
“…According to recent research evidence, the link between metabolic reprogramming and kidney disease may have a profound impact on disease progression and patient prognosis [3,4]. The metabolic-regulating effects of SGLT2 inhibition have been demonstrated; however, further investigation is required to elucidate the precise underlying mechanism [5].…”
Section: Introductionmentioning
confidence: 99%